Motivasi Kerja Aparatur Sipil Negara Pada Dinas Kehutanan Provinsi Sulawesi Tengah - Jisman, Jisman; Limbong, Martina (PARADIGMA : Jurnal Administrasi Publik, 2024)
This study aims to provide an overview of how the motivation of the State Civil Apparatus at the Forestry Service of Central Sulawesi Province. There were 5 informants in this study and one key informant. Data analysis techniques as usual qualitative research, namely data reduction, data presentation, and drawing conclusions. The results of the study indicate that: in the drive for achievement, employees strive to achieve the highest achievement, the problem is still the lack of fulfillment of facilities and infrastructure where operational vehicles are not adequate, as well as awards in the form of additional income and bonuses. In addition to the aspect of the drive to power, employees have the motivation to influence, the aspect that often occurs is the placement of positions that are not in accordance with their educational background or level of competence. Then from the aspect of encouragement to affiliate, namely with good cooperation, problems with the lack of closeness between superiors and subordinates or fellow co-workers and communication factors